Supporting the Growth and Spread of International Production Networks in Asia: How Can Trade Policy Help? - Jayant Menon (Asian Development Bank (ADB), 2013)
Free trade agreements (FTAs) have been proliferating in Asia for more than a decade. International fragmentation of production and the resultant cross-border production networks have been growing for a much longer period. Although FTAs are not necessary for the formation of production networks, can they support their further growth or spread? Empirical studies of this issue have produced mixed results, presumably because the causality can run either way. Therefore, this paper employs a qualitative approach that carefully examines the characteristics of both product fragmentation trade and FTAs in Asia to ascertain possible linkages. We find the relationship to be tenuous for a number of reasons. First, most product fragmentation trade already takes place at zero or low tariffs because of the International Technology Agreement, various duty-drawback schemes, and the location of most multinationals in duty-exempt export processing zones. Second, much of fragmentation trade is unlikely to benefit from FTA tariff concessions given the inability to satisfy rules of origin (ROOs) because of limited value-addition and/or classification problems relating to tariff-line shifting. Third, almost all FTAs involving Asian countries are relatively shallow, limiting their ability to promote production networks. Even if they were to deepen over time, it is difficult or costly to remove the non-tariff barriers that affect this trade in a preferential manner. For these reasons, it would be more useful if FTA preferences were multilateralized, and other accords were offered to all on most-favored nation basis. This, combined with national liberalization actions that deal with incumbency issues irrespective of nationality, would be the best way to support the growth of production networks involving current participants and the spread to new ones.
hdl:11540/2322
Keywords: F14; F15; F23; 330; Production networks; product fragmentation; free trade areas; trade facilitation; Asia